Emotional design pictures: Pleasant but too weak to evoke arousal and attract attention? - Lenski, Sina; Großschedl, Jörg (Frontiers in Psychology, 2023)
A new field of research builds on the theoretical assumption that distinct design manipulations, such as human-like features with appealing colors (emotional design), foster multimedia learning by influencing the learners’ affective state (i.e., valence, arousal) and attention. Empirical studies, however, provide inconsistent findings of the affective potential of emotional design, underlining the need for psychophysiological measurements to assess the affective state and attention more objectively. The effects of differently designed stimuli (picture-text combinations with anthropomorphic pictures in bright and saturated colors [emotional design], picture-text combinations with non-anthropomorphic pictures in grayscale [neutral design], and plain text [control design]) on junior high school students’ valence (N = 15), arousal (N = 18), and attention (N = 27) were examined. Valence was determined by students’ judgments on a rating scale; arousal and attention were assessed by psychophysiological parameters (electrodermal activity of students and their dwell time on stimuli, respectively). To allow the examination of valence and arousal as separate dimensions, two independent experiments were conducted. Results of experiment I show that students perceived emotional design stimuli as more pleasant than stimuli in neutral or control design. Besides, an interaction with the content of the stimuli was found. While the positive effect of the emotional design was found for concepts that could be interpreted as potentially positive (e.g., sunlight) or neutral (e.g., consumer), stimuli representing potentially negative concepts (e.g., dead consumer) were not perceived as more pleasant if presented in emotional design. Experiment II shows that emotional design did not induce higher arousal than neutral and control designs and did not attract more attention. Instead, the text within picture-text combinations (emotional and neutral designs) attracted more attention when pictures were presented in neutral than in emotional design. By investigating the emotional state more differentiated and by examining arousal and attention using psychophysiological parameters, the present study helps to understand the heterogeneous findings of previous studies.